2022
DOI: 10.3390/agriculture12070931
|View full text |Cite
|
Sign up to set email alerts
|

Plant Disease Detection and Classification Method Based on the Optimized Lightweight YOLOv5 Model

Abstract: Traditional plant disease diagnosis methods are mostly based on expert diagnosis, which easily leads to the backwardness of crop disease control and field management. In this paper, to improve the speed and accuracy of disease classification, a plant disease detection and classification method based on the optimized lightweight YOLOv5 model is proposed. We propose an IASM mechanism to improve the accuracy and efficiency of the model, to achieve model weight reduction through Ghostnet and WBF structure, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…MobileNetv2-YOLOv3 is a lightweight leaf disease detection network employed by Liu and Wang (2020). The disease detection method of Wang et al (2022b) is an optimized lightweight YOLOv5 (OL-YOLOv5). EADD-YOLO is the efficient and accurate network for detecting apple leaf disease proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MobileNetv2-YOLOv3 is a lightweight leaf disease detection network employed by Liu and Wang (2020). The disease detection method of Wang et al (2022b) is an optimized lightweight YOLOv5 (OL-YOLOv5). EADD-YOLO is the efficient and accurate network for detecting apple leaf disease proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the large number of convolution and bottleneck modules in the neck network results in the model still having many parameters. Wang et al (2022b) introduced the BiFPN structure to alleviate the low detection accuracy of the modified YOLOv5 but inevitably raised computational costs, which led to higher complexity. Although these crop leaf disease detection methods have attempted to optimize the structure of the network to improve computational efficiency, they do not make efficient measures to cope with the reduction in precision, resulting in low detection performance or only a slight decrease in model complexity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study provides no details regarding the number of the samples in the dataset. Another study published in [33], reported an accuracy of 92.57% using YOLOv5 model for classifying 61 categories of plant diseases that hit ten different plant species. The dataset consisted of 36,258 images.…”
Section: A Related Workmentioning
confidence: 99%
“…7 of YOLOv5 models. There are mainly three parts in the YOLOv5 object detecting models Backbone, Neck, and Head [23] which are already mentioned in Fig. 9 of the YOLOv5 architecture diagram.…”
Section: Object Detection Algorithms Yolov5mentioning
confidence: 99%